2015
DOI: 10.1007/s00264-014-2650-1
|View full text |Cite
|
Sign up to set email alerts
|

Nonoperative treatment of frozen shoulder: oral glucocorticoids

Abstract: Glucocorticoid therapy combined with pregabalin and a home exercise program is an effective treatment in the first stage of frozen shoulder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 17 publications
0
17
0
2
Order By: Relevance
“…Oral administration of corticosteroid is also used in the treatment of FS. Canbulat et al16) reported that oral glucocorticoids (0.5 mg/kg/day methylprednisolone) in 33 FS patients improved clinical outcomes: the mean visual analog scale (VAS) score, from 6.3 initially to 0.2 at 6-month follow-up; the mean Constant score, from 28.3 initially to 94.8 at first-year follow-up; the mean American Shoulder and Elbow Surgeons score, from 25.9 initially to 98.7 at first-year follow-up. In one randomized clinical trial of 40 patients performed by Lorbach et al,17) patients with idiopathic FS were treated with an oral corticosteroid treatment regimen (20 patients) or intra-articular injection of corticosteroid (20 patients).…”
Section: Conservative Treatmentmentioning
confidence: 99%
“…Oral administration of corticosteroid is also used in the treatment of FS. Canbulat et al16) reported that oral glucocorticoids (0.5 mg/kg/day methylprednisolone) in 33 FS patients improved clinical outcomes: the mean visual analog scale (VAS) score, from 6.3 initially to 0.2 at 6-month follow-up; the mean Constant score, from 28.3 initially to 94.8 at first-year follow-up; the mean American Shoulder and Elbow Surgeons score, from 25.9 initially to 98.7 at first-year follow-up. In one randomized clinical trial of 40 patients performed by Lorbach et al,17) patients with idiopathic FS were treated with an oral corticosteroid treatment regimen (20 patients) or intra-articular injection of corticosteroid (20 patients).…”
Section: Conservative Treatmentmentioning
confidence: 99%
“… 24 Other authors have demonstrated good outcomes in the early stages of frozen shoulder with oral steroids combined with neuropathic agents and a home exercise programme. 25 …”
Section: Current Treatment Optionsmentioning
confidence: 99%
“…Additionally, a review completed by Favejee et al supports the effectiveness of oral steroids compared with no treatment or placebo in the short term for adhesive capsulitis patients 11 . Canbulet et al completed a study of thirty-three patients who underwent oral steroid therapy combined with pregabalin and a home exercise program 19 . The study showed that patients had significant improvement in pain scores and ROM of the affected shoulder over a twenty-one month follow up period.…”
Section: Oral Pharmacological Therapymentioning
confidence: 99%